Argon plasma coagulation treatment of anal high‐grade squamous intraepithelial lesions in men who have sex with men living with HIV: results of a 2‐year prospective pilot study. Issue 2 (23rd August 2017) - de Pokomandy, A; Rouleau, D; Lalonde, R; Beauvais, C; de Castro, C; Coutlée, F; ,
Abstract : Objectives: Men who have sex with men (MSM) living with HIV are at high risk for anal high‐grade squamous intraepithelial lesions (HSILs) and cancer. The best management of anal HSIL remains unclear. Our objective was to assess whether argon plasma coagulation (APC) could be safe, well tolerated and efficient to treat anal HSILs in MSM living with HIV. Methods: A prospective phase II, open‐label, pilot study was conducted to evaluate APC to treat anal HSILs in 20 HIV‐positive MSM. Participants were followed for 2 years after their first treatment. Results: Twenty men with persistent HSILs completed the 2‐year study. Their baseline median CD4 count was 490 cells/μL and 85% had undetectable HIV viral loads. Overall, 65% (13/20) of participants were clear of HSILs at their 24‐month visit. The initial response rates after the first, second and third APC treatments were 45%, 44% and 67%, respectively, but recurrences were common. The main side effect was pain during and within 1 week after the treatments. There were no long‐term side effects, nor serious adverse events related to the procedure. Cost is a drawback. Conclusions: APC can be used to treat anal HSILs in HIV‐seropositive MSM, and requires repeated treatment because of a high recurrence rate. As successful treatment of human papillomavirus (HPV) infection or eradication of the anal transitional zone remains impossible, HSIL treatment is challenging and requires long‐term follow‐up.